Usefulness of Endoscopic Managements in Patients with Ceftriaxone-Induced Pseudolithiasis Causing Biliary Obstruction - Yasuhiro Doi; Yasushi Takii; Hiroyuki Ito; Norihiko Jingu; Kentaro To; Sinichiro Kimura; Koichi Kimura; Kensaku Sanefuji; Hirofumi Ikeda; Sayaka Tachibana; Takeshi Otsuka (Case Reports in Medicine)
Ceftriaxone (CTRX) is known to cause reversible biliary stones/sludge, which is called biliary pseudolithiasis. We report two rare cases of biliary obstruction by pseudolithiasis shortly after completing CTRX treatment. Stones and sludge, which had not been detected before CTRX administration, appeared in the gallbladder and common bile duct and led to biliary obstruction and acute cholangitis. The obstructions were successfully treated with endoscopic retrograde biliary drainage and endoscopic sphincterotomy. CTRX-induced biliary pseudolithiasis has been reported mainly in children and adolescents but is also seen in adults with similar incidence rate. Although CTRX-induced biliary pseudolithiasis is usually asymptomatic and disappears spontaneously after discontinuing the drug, some patients develop biliary obstruction. Endoscopic managements should be considered in such cases.